Teachers' Perceptions On The Use of Digital Games to Support Young Learners Vocabulary Learning - Urnila, Sinta; Sri Wulandari; Prasongko, Angga (Jurnal Pendidikan Anak, 2024)
Digital games are not only used as stress relievers but are often used as learning media. And one of the digital games used as a learning medium is wordwall. wordwall is a web-based digital game application that provides various features such as matching information, images, quizzes, wheel of fortune, puzzles, etc. and can be used for teaching, including teaching English vocabulary. And the aim of this research is to find out What games do teachers often use to support vocabulary learning, What is teacher's perception of the use and suitability of digital game content to support vocabulary learning, What obstacles do teachers face when using digital games to support vocabulary learning , What solutions can be done to overcome these obstacles. This research was carried out in 3 elementary schools in the city of Kediri, including: SD Negeri Kaliombo, SDN Ngronggo 3, and SDN Ngronggo 6. Apart from that, the method used in this research is a qualitative research method with the data collection techniques used are interviews, observation and documentation. The results of this research are that wordwall is a digital game that can be used to support vocabulary learning. And learning carried out using digital games is very effective and interesting with a variety of content available and appropriate to the level of students. Even so, there are still several obstacles when using digital games, such as: limited time, slow internet connection, and difficulty managing students. And to overcome these obstacles, teachers will organize as much time as possible to create lesson materials, provide personal internet data, and form students into small groups.